The Asymmetric and Long-Run Effect of Financial Stability on Environmental Degradation in Norway - Kirikkaleli, Dervis; Castanho, Rui Alexandre; Genc, Sema Yilmaz; Oyebanji, Modupe Oluyemisi; Couto, Gualter (MDPI, 2022)
Risks associated with climate change can have an injurious impact on the economy as well as the financial system as a whole. There is a possibility that certain risks, such as losses to financial intermediaries and disruptions in the functioning of financial markets, can aggravate vulnerabilities in the financial system under certain conditions, including sudden increases in the prices of large asset classes. Using the dataset for Norway between 1995 and 2018, this study investigates how financial stability affects environmental degradation in Norway while controlling openness in trade, ecological clean energy, and economic growth. Findings from the results demonstrate that (i) financial stability causes a reduction in environmental degradation; (ii) growth causes carbon emissions to climb significantly; and (iii) renewable energy has been favorable for emissions in Norway. Lastly, surprisingly, trade openness causes a decline in carbon emissions. The study recommends that since financial stability in Norway reduces environmental degradation by incorporating climate-related risks into the financial stability monitoring framework, it can contribute to lowering carbon emissions to a greater extent. Norway's policymakers should conduct detailed analyses of the role of global emissions in long-term petroleum policy and the economic viability of selected climate policy scenarios before implementing such a policy. Moreover, policymakers should be updated on the financial system's vulnerabilities, considering climate-related shocks are likely to affect all financial systems. In addition, policymakers should encourage the use of sustainable energy to raise the availability of reliable, affordable, and sustainable energy to everyone.
Keywords: financial stability; environmental degradation; economic growth; trade; Norway; ECONOMIC-GROWTH; CO2 EMISSIONS; KUZNETS CURVE; ENERGY; CONSUMPTION; OPENNESS; Science & Technology - Other Topics; Environmental Sciences & Ecology